RECRUITMENT AS A COMPONENT OF THE DIGITAL STRATEGY OF PERSONNEL MANAGEMENT - SKIBSKA, Kateryna; PANASIUK, Oleksandra (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article provides an overview of state-of-the-art recruiting automation systems that help companies conduct more effective and efficient work with personnel. The analysis of research and scientific works showed that this topic is gaining momentum every year, does not lose its relevance, but has not been studied at a deeper level. It has been established that there are currently many software offers on the market, which are designed for different sizes of companies and budgets and have various functionalities. New technologies appear every year, thanks to the development of digital transformation of personnel management business processes. The description of the functionality of the most common systems presented in the article will help companies analyze the effectiveness of each and choose a product specifically for solving their own urgent problems. It was found that currently companies do not use these opportunities sufficiently, because they do not always have the resources for this and are sufficiently knowledgeable about this issue. Despite this, more and more companies are beginning to understand the potential of using automated systems to improve the process of finding and hiring qualified job candidates, so this topic will be relevant in the near future. Moreover, the labor market is currently going through difficult times due to the large number of labor migrants and insufficient number of qualified personnel. The use of modern automation systems will allow companies to optimize business — personnel management processes, in particular, and recruiting, which will improve the quality of personnel at the entrance and improve the performance of personnel recruitment. As a conclusion, the penetration of digital technologies, cloud computing, artificial intelligence, remote work, etc. into our lives are changing approaches to personnel recruitment, so in order to remain competitive, companies should pay special attention to this issue.